POLA PEMBINAAN MURID KRISTEN DI ASRAMA PUTRI SMK BAGIMU NEGERIKU - Yolanda natalia; Fianus Tandiongan; Didasgil Taneo (STT Kristus Alfa Omega, 2020)
The coaching pattern is a role of parents or coaches to play an important role for the development of children both in the academic field and character, by providing guidance and experience and providing supervision so that children can face the life to come better. The research objective was to determine the extent of the pattern of coaching students at SMK Bagimu Negeriku Semarang. The results of the hypothesis proposed in this study are: the development pattern is suspected to be in the moderate category or ? 70% is not accepted. Because the results found exceeded expectations, namely by 88%.